Benefits of a 3-month cycle of weekly virtual museum tours in community dwelling older adults: Results of a randomized controlled trial - Beauchet, Olivier; Matskiv, Jacqueline; Galery, Kevin; Goossens, Linda; Lafontaine, Constance; Sawchuk, Kim (Frontiers in Medicine, 2022)
Background Museums can be instrumental in fostering social inclusion and may improve the overall health of the older population. Over the course of the 2019 coronavirus pandemic, many older adults suffered as a result of confinement measures, which may have accelerated the processes that lead to physical frailty and increased mental health risks. This study aims to examine whether a 3-month cycle of weekly virtual tours of the Montreal Museum of Fine Arts (MMFA) may have improved feelings of social inclusion, wellbeing and quality of life, and reduced physical frailty in older adults living within the community of Montreal. Methods and design A total of 106 older adults, who were community-dwellers living in Montreal (Quebec, Canada), were recruited for a randomized controlled trial in two parallel groups (intervention with n = 53 vs control with n = 53) between January and April 2022. The intervention consisted of a 3-month cycle of weekly virtual museum tours of the MMFA. Social isolation, wellbeing, quality of life and frailty were evaluated using validated scales that were assessed on a web platform at baseline (M0) and after 3 months (M3) in the intervention group. The control group completed the same assessment according to the same schedule. The outcomes were the mean scores at M0 and M3, and changes in mean scores between M0 and M3. Results The intervention group showed significant improvements in their social isolation, wellbeing, quality of life and frailty scores when compared to the control group, the highest benefits being observed with frailty. Conclusion The results suggest that the 3-month cycle of weekly virtual MMFA tours may improve social inclusion, physical and mental health in community-dwelling older adults living in Montreal. Trial registration https://clinicaltrials.gov/ct2/show/NCT05046288, identifier NCT05046288.